Do urban safety net programs affect the financial inclusion and food security of households, primarily women participating in urban agriculture? A triangulative exploration of Ethiopia - Tareke, Kassa Moges (Frontiers in Sustainable Food Systems, 2025)
Throughout the world, poverty, income inequality and food insecurity in urban areas have continued to be pressing issues. As a solution, a productive urban safety net program has been launched to provide conditional cash transfers (CTs) to poor households since 2017 in urban areas of Ethiopia. This study examines the impact of CTs made by the program to beneficiary households on the financial inclusion options, participation in urban agriculture and levels of food security among women in Addis Ababa, Ethiopia. Random stratified sampling was used to select 278 women for questionnaire surveys. Mixed research, comparative impact analysis, food security index, Ordinary Least Square (OLS), Logistic, and Ordinal Probit regressions were applied. Results showed that 94% of respondents could have ownership of a bank account and participated in urban agriculture as additional income source only after receiving CTs from the program. This contributed to better access to other financial inclusion components such as saving, credit, mobile banking, advice on finance management, and farm incomes. The study found that 171 (61.5%) women households were food insecure, while 107 (38.5%) were food secure. The minimum, maximum, and mean K/calorie consumed by food-insecure female farmers was 674.6, 2082.1, and 1378 Kcals, respectively, while 2192.5, 5360.4, and 3776.6 Kcals for food-secure ones. Furthermore, mean calorie consumption of women also significantly varies with the type of urban agriculture they are involved in. Accordingly, among the food-secure women, the mean calorie consumption was relatively better in those involved in horticulture relative to animal husbandry. The OLS model indicate the coefficient of bank account ownership, amount saved in the last 1year, farm income and proportion of credit used for actual collection intention have a significant positive effect on food security index. The logistic regression model also confirmed that among the financial inclusion options, amount saved, advice on finance management, and proportion of credit used were the most significant predictors. The safety net program’s CTs have moderately improved financial inclusion for women and slightly increased food-secured women, but their overall contribution to food security remains inadequate, as a significant portion of women’s households still experience food insecurity and poor urban agriculture. The study implies urban planning and development policies still need to be more pro-poor, gender-sensitive & responsive & inclusive to bring majority of urban women households out of food insecurity by improving their nutrition calorie consumption & job via urban agriculture. Accordingly, it informs partners to revisit and expand the safety net program scope, consider more financial inclusion options and urban agriculture facilities, including soft loan provisions, grants, Agri-input, market links, training, incentives, and increasing CTs amount. Besides, business-to-business networking events among financial service providers is essential to create long-term partnerships to improve financial services, access to agricultural technology and income-generating job options including Agri-Micro Small and Medium Enterprises to urban poor, particularly women program beneficiary households. Organization of further research with wider scope is also necessary.